Study of serum ferritin levels in preterm labour and its perinatal outcome in tertiary care centre (Panacea Journal of Medical Sciences, 2024)
Background: Pregnant women at risk of preterm birth may be easily identified and sent to tertiary care centres for further therapy. Numerous biomarkers are being investigated for their ability to predict preterm labour; serum ferritin is one of these indicators. It is an intracellular protein that has a role in iron storage and is also an acute phase reactant that is increased during acute and chronic infections.Objective: To evaluate serum ferritin levels in preterm labour and perinatal outcome in a tertiary care centre during 2 years.Materials and Methods: A case control study was conducted in collaboration with the Department of Obstetrics and Gynecology at Osmania Medical College, Hyderabad, from 2019 to 2022. After receiving permission, one hundred participants with an average age of 25 years who visit Niloufer hospital are included in the research and separated into case (Group 1) and control (Group 2) groups. Group 1 consists of women who had spontaneous preterm labour, whereas Group 2 consists of pregnant women of the same gestational age who are considered controls.Results: Among 50 instances of preterm labour, 39 (78.0 percent) were classified as preterm (32 to 36 weeks), whereas 11 (22.0 percent) were classified as very preterm (28 to 32 weeks). The majority of the 50 patients included in the research, 31 (62.0 percent), were born by normal vaginal delivery, while 19 (38.0 percent) were delivered using emergency LSCS. CRP was positive in two patients (4.0 percent). The mean WBC levels in cases were much greater than those in controls, and the difference is statistically significant. Serum ferritin levels were 40.298 19.64 in cases and 20.343 6.82 in controls. Serum ferritin levels were substantially higher in cases than in controls on average. The mean WBC levels were greatest in extremely preterm infants, followed by preterm infants; however, this difference was determined to be statistically insignificant.Conclusion: Ferritin levels are much higher in preterm labour patients than in low-risk women of the same gestational age. Serum ferritin levels may be utilised as a biomarker in high-risk premature labour.